P.090 Symptomatic neonatal seizure treatment duration and seizure recurrence: a retrospective single center study. (June 2022) - Martinez, A; De Carolis, M; Marandyuk, B; Tremblay, S; Lodygensky, G; Birca, A; Pinchefsky, E
Abstract : Background: While seizures have adverse neurological effects, the prescribed antiseizure medications (ASMs) may also have a negative impact on neonatal brains and contribute to detrimental neurodevelopmental outcomes. The objectives were to evaluate: 1) the impact of implementing a neonatal seizure treatment protocol in 2016; 2) the influence of ASM duration and other clinical factors on seizure recurrence and epilepsy onset. Methods: Retrospective chart review of 139 term newborns born between 2013 and March 2021 admitted at Sainte-Justine University Center Hospital with acute symptomatic seizures. Associations were assessed using Student T-test and Fisher exact test. Results: We did not observe significant change in the number of ASMs prescribed for acute seizure control (33% required 33 ASMs before vs 22% after 2016) nor significant change in frequency of prescription of ASM at discharge over time. ASM continuation at discharge was not associated with seizure recurrence (p=0.14, OR 2.14, 95%CI 0.78-5.86) or epilepsy (p=0.78, OR 1.32, 95% CI 0.45-3.90). Epilepsy occurred in 15 (12%) of children between 15 days to 72 months of age. Conclusions: No association was found between ASM maintenance at discharge following acute symptomatic neonatal seizures and the occurrence of epilepsy. Discontinuation of ASMs should be considered prior to discharge.